Inflation and Food Prices in Albania, Western Balkans and EU: A ‎Comparative Analysis Before and After COVID-19 - Stringa, Azmi; Gjata, Idlir; Korbi, Alban (International Journal of Accounting and Economics Studies, 2025)
By 2024, Albania’s food and non-alcoholic beverage prices reached 100% of the EU average, up from 68% in 2012, despite a nearly 30% ‎appreciation of the local currency. This was the sharpest increase in food prices recorded in the Balkans during the period, despite the country recording similar growth rates to the regional average. Food prices in Albania are today at levels higher than in countries such as the ‎Netherlands and Spain, which have significantly higher GDP per capita and household wellbeing than Albania (GDP per capita at 35% of ‎the EU average, second from last in the Balkans). In 2024, Albanian families, who allocate nearly 40% of their income to food, face price levels comparable to those of much wealthier EU households. This study provides a robust, regression-based comparative analysis of food price inflation ‎in Albania from 2013 to 2024, benchmarking trends against the European Union (EU), key EU trade partners (Italy, Greece, Germany), and ‎Western Balkan economies. It compares food inflation dynamics across two periods, pre-COVID (2013–2021) and post-COVID (2022–‎‎2024), and evaluates the role of currency appreciation in moderating domestic price pressures. Using harmonized consumer price data and ‎exchange-rate-adjusted regression models, the study reveals that Albania’s food prices have risen earlier, faster and more persistently than in ‎its peer countries, even as the Albanian lek appreciated nearly 30% over the decade. While food price movements in Albania appear to align ‎with EU trends, statistical modeling shows a significantly stronger elasticity and an amplified domestic response, particularly before 2021. ‎Once exchange rate effects are accounted for, Albania’s correlation with EU food prices collapses, unlike in other Western Balkan countries ‎or EU trade partners, indicating that FX gains were not passed on to consumers. These findings provide strong empirical evidence that Albania’s inflation outcomes are not simply imported but are domestically amplified due to weak market competition, non-transparent pricing, and limited regulatory oversight. The paper concludes that internal structural issues have muted the pass-through benefits of currency appre‎ciation to consumers, while price increases closely followed the trend observed in the EU. This underscores the need for stronger competi‎tion policy and more inclusive market mechanisms to ensure that macroeconomic gains support household welfare. The paper is especially ‎relevant to policymakers, central banks, international institutions, and researchers seeking to understand how structural inefficiencies can ‎offset macroeconomic advantages in small economies‎.
Keywords: Economic Growth; Foreign Currency Exchange; Covid-19; Household Index of Consumer Prices; Household Welfare